2015
DOI: 10.1111/ggi.12473
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic neuropathy: The hidden cardiovascular comorbidity in elderly patients with chronic obstructive pulmonary disease attending primary care settings

Abstract: COPD has a complex spectrum of comorbidities. Cardiac autonomic neuropathy in elderly male patients with COPD correlated with hypercapnia, but not hypoxemia or the disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Rasheedy et al examined elderly outpatients with COPD and measured heart-rate and blood-pressure response to different stimuli. It was found that among patients with cardiac autonomic dysfunction, a higher baseline heart rate and higher CO 2 levels represented severity of the disease 36. The data from our study revealed higher bicarbonate levels in the prolonged-QTc group, which might represent the chronic compensation of CO 2 retention found in severe COPD patients.…”
Section: Discussionsupporting
confidence: 48%
“…Rasheedy et al examined elderly outpatients with COPD and measured heart-rate and blood-pressure response to different stimuli. It was found that among patients with cardiac autonomic dysfunction, a higher baseline heart rate and higher CO 2 levels represented severity of the disease 36. The data from our study revealed higher bicarbonate levels in the prolonged-QTc group, which might represent the chronic compensation of CO 2 retention found in severe COPD patients.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, it was considered as a probable pathogenetic mechanism behind increased mortality in patients with diabetes mellitus. CAN-related morbidity and mortality have also been researched in other diseases, including familial dysautonomia [ 15 ], Ehlers-Danlos syndrome [ 16 ], chronic obstructive pulmonary disease [ 17 ], liver cirrhosis [ 18 ], hypertension and hyperuricemia [ 19 ]. Furthermore, it was shown to predict all-cause mortality and sudden death in patients with chronic heart failure following ischemic or idiopathic dilated cardiomyopathy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between CAN and morbidity as well as mortality was also examined in other diseases that affect the autonomic nervous system. Apart from congenital diseases, such as familial dysautonomia and Ehlers-Danlos syndrome, 31 , 32 was associated with chronic obstructive pulmonary disease, 33 liver cirrhosis, 34 hypertension, and hyperuricemia. 35 In patients with chronic heart failure secondary to ischemic or idiopathic-dilated cardiomyopathy, the presence of , as identified by reduced uptake of metaiodobenzylguanidine labeled with iodine-123 or by pathological HRV measurements, was shown to predict all-cause mortality and sudden death.…”
Section: Discussionmentioning
confidence: 99%